(untitled) (Research, Society and Development, 2021)
Faced with a new logistical system for the collection and disposal of solid urban waste applied in the Recanto dos Humildes Region in the District of Perus/SP, the main objective of this work was to identify Environmental Perception (PA) and measure the willingness to pay for a sample composed of those favored by this new system. In addition, a generalized linear model was proposed to infer the relationship between environmental perception and socioeconomic variables, willingness to pay and evaluation of the new logistical system for the collection of solid waste. The methodology used was the application of a questionnaire to a sample composed by the residents of the region under study and econometric modeling for data treatment. Among the chosen predictor variables, those rel. ted to the waste collection and socioeconomic system (sex, age, education and income) were statistically significant to explain the interviewees’ PA. Regarding the willingness to pay, it was found that approximately 63% of respondents would pay some amount for the service offered by the new logistical collection and disposal system for urban solid waste.